caracterização do ciclo de multiplicação de Mayaro Virus (MAYV) e análise dos potenciais efeitos antivirais de inibidores de vias de sinalização in vitro e in vivo - Diogo Correa Mendonca (2022)
Mayaro virus (MAYV) belongs to the genus Alphavirus, family Togaviridae, that also includes CHIV. MAYV is mainly found on Central and South America and is transmitted by mosquitos from the Haemagogus genus causing a febrile illness followed by a debilitating arthritis and arthralgia similar to the one caused by CHIV. The Mayaro fever can lead to sequelae that have a direct impact on the patient's productive capacity for long periods of time which can lead to serious economic damage, such as that which has occurred with CHIKV in recent years. The Mayaro fever is considered a neglected disease due to the few epidemiological data and in Brazil it is considered a potential public health risk with increasing numbers of cases increasing every year. As with most arboviruses, there is no treatment or vaccine for MAYV, and their development is necessary in the face of a future epidemic. The main objectives are characterizing the stages of MAYV replication cycle establishing a event tiemeline and to evaluate the potential of Pharmacological Inhibitors (PIs) against infection with MAYV in vitro and in vivo in animal model. For the characterization, multiplication curves with MOI 10 – 0.1 were made for analysis by titration in plaque assay, qPCR and transmission electron microscopy (TEM). The virus had a rapid cycle, a period of eclipse around 4 h.p.i. followed by an exponential increase in the number of particles lasting between 3 and 18 hours and a stationary phase after 24 hours. TEM images using MOI 10 revealed particles penetrating the cell between 30 m.p.i. and 1 h.p.i., uncoating 2-3 h.p.i, appearance of spherules 4 h.p.i., and cytoplasmic vacuole II (CPV-II) 5 h.p.i., liberation started 4 h.p.i. increasing exponentially 6 h.p.i. With our data we were able to stablish a chronological order of events during MAYV replication including uncharacterized steps as ribosome reorganization, early clusters of viral precursors and a secondary way of particle release, through exocytosis inside giant forms. For the inhibition assays, MAPK PIs were tested, with a 90% reduction in viral load at 15 h.p.i with MOI 0.1, for the inhibitors, Trametinib (MEK / ERK) and JNK-VIII and reduction in 82% in the number of particles observed in MET (Trametinib only). We also carried out pilot experiments with animal models using C57BL/6 and using an infection model with mice 15-18 days old infected with MAYV. Trametinib was able to reduce the mortality rate by 75% with the administered dose (2mg/ kg) that was tolerable for these animals. In addition, it caused a delay in the appearance of signals and a reduction in the genomic load observed in the liver (42%), spleen (59%) and brain (100%). In conclusion, our work demonstrates the antiviral potential of two PIs: Trametinib (in vitro and in vivo) JNK VIII (in vivo), for MAYV and characterizes stages of the multiplication cycle, with unpublished MET images for MAYV